Effect of Phase Feeding Budget and Weaning Weight on Nursery Pig Growth Performance and Economics: A Follow-Up Study - Julian Arroyave; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
This experiment was conducted to validate the results of a previous study that observed no difference in overall growth performance, but better economic outcomes when a simple phase feeding program was used compared to a more traditional complex program. At weaning, a total of 360 pigs (initially 13.3 ± 0.36 lb) were sorted by body weight (BW) and then randomly assigned to one of three dietary treatments arranged in a 3 × 3 factorial. Main effects included nursery phase feeding budget (high, medium, or low) and BW category (light, medium, or heavy). There were five pigs per pen and 12 pens per treatment. The feed budgets for phases 1 and 2 were 4, 2, 0, and 12, 8, 4 lb/pig for high, medium, and low nursery feeding budget programs, respectively. All pigs were then fed a common phase 3 diet thereafter. Phase 1 was formulated with specialty animal protein and lactose products and was formulated to contain 18.0% lactose with 16.3% soybean meal. In phase 2, specialty protein sources and the lactose level were reduced, with diets containing 7.2% lactose and 22.5% soybean meal. Phase 3 was a common corn-soybean meal-based diet with no specialty protein or lactose sources. Through the course of this trial, pigs were in good health with no mortality or removals. No interactions were observed between phase feeding budget and BW category for any response criteria. Overall (d 0 to 43), pigs fed with the low-budget program had greater (P < 0.05) ADG than those fed the high-budget program, with pigs fed the medium budget program intermediate. No differences in ADFI were observed among feed budget programs. Pigs fed the low-budget program tended (P = 0.054) to have improved F/G compared with those fed the high-budget program, while pigs fed the medium-budget program were intermediate. Feed cost and feed cost/lb of gain decreased as the phase 1 and 2 feed budgets were reduced (P < 0.001). There was a tendency (P = 0.077) for increased revenue with decreasing feed budget; however, no pairwise differences between treatments were observed. Income over feed cost improved (P < 0.001) as the phase feeding budgets decreased. For BW category, d 42 BW, ADG, and ADFI increased (P < 0.001) as the initial BW increased. However, no differences in F/G were observed between any BW category. Also, economic criteria improved (P < 0.001) as weaning BW category increased. In conclusion, in healthy pigs, the use of low phase 1 and 2 feed budget programs resulted in an overall improvement of ADG and F/G. Economics improved as simpler feed budgets were used. Finally, pigs that were heavier at weaning had better overall nursery performance and economic returns than lighter-weight weaned pigs.
Keywords: Feed budget; growth performance; nursery pig; phase feeding; weaning weights